The effect of the self-questioning strategy on developing contemplative thinking skills in Islamic education for female second Grade Secondary Students in Aqaba Governorate Jordan - Alhabahbeh, Basmah Abdallah Odeh (Journal of Educational and Psychological Sciences, 2020)
The current study aimed to identify the effect of the self-questioning strategy on developing contemplative thinking skills in Islamic education for female second Grade Secondary Students in Jordan. The study adopted the quasi-experimental approach, and the tool was a (contemplative thinking skills test), prepared by the researcher, which was applied to a random sample of two divisions from second Grade Secondary Student in the comprehensive secondary school for girls, affiliated to the Directorate of Education in the Aqaba Governorate during the academic year 2019/2020 Division C, as an experimental group, consisted of (30) students, and Division B as a control group, consisting of ( 30) students. The results of the joint variance analysis (ANCOVA) showed that there were statistically significant differences between the average of the students ’scores on the achievement test attributed to the variable of the teaching method, where the control group obtained a total average (12.03of 25) in exchange for the experimental group obtaining a total average (17.25of 25), and in favor of the group Experimental, and in light of the results of the study, the researcher recommended training the teachers on the self-questioning strategy in teaching Islamic education for its effectiveness in teaching and conducting studies dealing with the introduction of other teaching methods.
Keywords: Self-Questioning Strategy; Meditative Thinking; Islamic Education; second Grade Secondary Students